A Research Agenda for COVID-19 and Society - Matthewman, Steve (Edward Elgar Publishing, 2022)
This is an open access title available under the terms of a CC BY-NC-ND 4.0 License. It is free to read, download and share on Elgaronline.com. With contributions from leading experts in the fields of anthropology, communications, disaster studies, economics, epidemiology, Indigenous studies, philosophy and sociology, this expansive book offers a diverse range of social science perspectives on the COVID-19 pandemic, providing critical insights into what a research agenda for COVID-19 and society resembles across different fields of study.